Effect of compaction parameters on the physical properties of zinc oxide varistor discs - Karim, A.N. Mustafizul; Puyane, R.; El-Baradie, M.A; Hashmi, M. S. J. (Nanyang Technological University, 1995)
A homogeneous compact body with higher green density and less gradient is expected to yield a uniform body with higher fired density and minimum shape distortion. Compaction parameters are optimised accordingly to achieve the necessary green property. There are various parameters in the process of powder compaction. Nevertheless, the present study has been confined to only.two significant variables - compacting stress and speed. It has already been established that higher compaction stress for a particular speed or lower pressing speed for a particular stress leads to higher green density. However, the effect of these parameters following sintering does not remain the same. This study with two level factorial design has been performed to observe systematically the effect of compaction stress and speed on the physical properties of the varistor discs both at the green as well as at the fired state. Green discs prepared from standard zinc oxide varistor powder were sintered in a pot kiln and in a single run to avoid the variation of sintering influence on different samples. Discs pressed with lower speed eventually exhibited lower fired density in contrast to their slightly higher green density. Other sintering features such as shrinkage, dimensional deformation in the form of mid-height depression are also found to be dependent on these parameters.